2011
DOI: 10.4104/pcrj.2011.00003
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric asthma outpatient care by asthma nurse, paediatrician or general practitioner: randomised controlled trial with two-year follow-up

Abstract: Aims: For children with stable asthma, to test non-inferiority of care provided by a hospital-based specialised asthma nurse versus a general practitioner (GP) or paediatrician.Methods: Randomised controlled trial evaluating standard care by a GP, paediatrician or an asthma nurse, with two-year follow-up.Results: 107 children were recruited, 45 from general practice and 62 from hospital. After two years, no significant differences between groups were found for airway responsiveness, FEV1, asthma control, medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 28 publications
0
41
0
1
Order By: Relevance
“…11,13 In addition, a Dutch study showed that care provided by a specialised asthma nurse is as effective in the outpatient management of stable childhood asthma as traditional management by a paediatrician or GP. 43 Furthermore, attention to clinical guidelines can improve evidence-based nursing practice in connection with the non-pharmacological management necessary for optimal treatment of childhood asthma in which specialised asthma nurses are highly skilled. 44 Despite the obvious importance of a planned follow-up visit for asthma control as emphasised in national guidelines, only half of the children had a planned follow-up.…”
Section: Interpretation Of Findings In Relation To Previously Publishmentioning
confidence: 99%
“…11,13 In addition, a Dutch study showed that care provided by a specialised asthma nurse is as effective in the outpatient management of stable childhood asthma as traditional management by a paediatrician or GP. 43 Furthermore, attention to clinical guidelines can improve evidence-based nursing practice in connection with the non-pharmacological management necessary for optimal treatment of childhood asthma in which specialised asthma nurses are highly skilled. 44 Despite the obvious importance of a planned follow-up visit for asthma control as emphasised in national guidelines, only half of the children had a planned follow-up.…”
Section: Interpretation Of Findings In Relation To Previously Publishmentioning
confidence: 99%
“…Written informed consent was obtained from all parents and from patients 12 years and older. This study was part of a more extended trial about the follow-up in the denominated settings (21,22) (see consort diagram).…”
Section: Patientsmentioning
confidence: 99%
“…In the UK, credit for facilitating this transfer of management from secondary to primary care can be shared by visionary drivers in the General Practitioners in Asthma Group (now the Primary Care Respiratory Society UK, PCRS-UK), the National Asthma Training Centre (now Education for Health), and the support of some wise, thoughtful and nonthreatened secondary care opinion leaders. 1 In this issue of the Journal, Kuethe et al 2 develop the evidence base for alternative models of health care delivery for the management of chronic asthma in children by clinicians of different crafts -paediatrician, GP or (hospital-based) specialist nurse. The rather technical primary endpoint, airway hyper-responsiveness as measured by methacholine challenge, demonstrated non-inferiority between the groups.…”
mentioning
confidence: 99%
“…4 These standards, mandatory in Scotland, call inter alia for systems to identify and manage high risk children and young people with asthma, such as those with frequent visits to emergency centres or out-of-hours contacts, or those who are prescribed or appear to require above-licensed doses of ICS. This 2 Even the most reactionary of clinicians should be reassured by a system for allocating patients to a nurse for follow-up which includes confirmation by a doctor of the diagnosis of asthma (although, of course, this is not by definition infallible; diagnoses of asthma in children should always be questioned and the evidence for making the diagnosis recorded), the exclusion of more severe cases, and an insistence that management guidelines are strictly followed. Equally heartening is that nurses still sought specialist support when necessary.…”
mentioning
confidence: 99%
See 1 more Smart Citation